2012
DOI: 10.1371/journal.pone.0036078
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Screening Instrument for Autism Spectrum Disorders in Prisoners

Abstract: There have been concerns that individuals with autism spectrum disorders (ASDs) are over-represented but not recognised in prison populations. A screening tool for ASDs in prisons has therefore been developed.AimsWe aimed to evaluate this tool in Scottish prisoners by comparing scores with standard measures of autistic traits (Autism Quotient (AQ)), neurodevelopmental history (Asperger Syndrome (and High-Functioning Autism) Diagnostic Interview (ASDI)), and social cognition (Ekman 60 Faces test).MethodsPrison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 24 publications
2
63
0
1
Order By: Relevance
“…Other studies have sought to obtain information on ASD using prison staff as informants (Robinson et al 2012) or self-rating screening tools (Fazio et al, 2012). These studies have tended to find lower rates of ASD traits than the current study.…”
Section: Limitations and Strengthsmentioning
confidence: 77%
“…Other studies have sought to obtain information on ASD using prison staff as informants (Robinson et al 2012) or self-rating screening tools (Fazio et al, 2012). These studies have tended to find lower rates of ASD traits than the current study.…”
Section: Limitations and Strengthsmentioning
confidence: 77%
“…In fact, the prevalence rate of ASDs in prisons is unknown (Robinson et al, 2012). The social and physical constraints of the prison environment can result in numerous problems for inmates with ASDs.…”
Section: Individuals With Asd's Experience Within Prison Environmentmentioning
confidence: 99%
“…Their review only identified four articles. One study involved an evaluation of a screening tool for individuals with ASDs in prisons (Robinson et al, 2012), so was not focused on the experience of individuals with ASD in the prison environment. One investigated the knowledge of ASD among prison staff (McAdam, 2009).…”
Section: Individuals With Asd's Experience Within Prison Environmentmentioning
confidence: 99%
“…Robinson et al . () reported that there was no evidence to suggest that ASD was over‐represented in the Scottish prison population, whereas a screening study in a North American maximum security prison ( n = 431) reported a rate of 4.4% (four times greater than in the general population) (Fazio et al . ).…”
Section: Introductionmentioning
confidence: 97%